Rare earth high-iron aluminum alloy strip

By adding rare earth elements and high iron content to the aluminum alloy strip and using nitriding and anodizing treatment technology to form a protective coating, the problem of insufficient strength and corrosion resistance of the aluminum alloy strip is solved, and the coordinated improvement of mechanical properties and corrosion resistance is achieved, which is suitable for the protection of cable cores.

CN119786123AActive Publication Date: 2025-04-08WENZHOU ANNENG TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510280437.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

The existing aluminum alloy strips are insufficient in terms of tensile strength, flexibility and corrosion resistance, and it is difficult to improve strength and corrosion resistance at the same time.

Method used

A rare earth high-iron aluminum alloy strip is used to form a new reinforced frame through an aluminum matrix and high-content iron, and the surface is nitrided and then anodized to form a protective coating to improve mechanical properties and corrosion resistance.

Benefits of technology

The mechanical properties of rare earth high-speed iron aluminum alloy strips have been improved, including tensile strength, flexibility and ductility, while improving corrosion and wear resistance, which is suitable for the winding protection needs of cable cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a rare earth high-ferro-aluminum alloy strip which comprises a strip body, and the strip body comprises the following components: 4-6 wt% of Fe, 1.1-1.3 wt% of Ce and the balance of Al; 0.7 to 0.9 wt% of Y; 0.5 to 1 wt% of Mg; 0.3 to 0.7 wt% of Si; 0.1 to 0.3 wt% of Zr; and the balance of aluminum and inevitable impurities. The surface of the strip body further comprises a protective coating film formed by nitriding treatment and anodic oxidation treatment on the surface of the strip body, compared with the prior art, the rare earth high-ferro-aluminum alloy strip guarantees good flexibility meeting the requirement of the strip for wrapping a cable core, meanwhile, the rare earth high-ferro-aluminum alloy strip further has the excellent mechanical property and high corrosion resistance, the service life of the strip is prolonged, and the service life of the strip is prolonged. And the cable core winding protection requirement can be well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an alloy strip for cable shielding, in particular to a rare earth high iron aluminum alloy strip Background Art

[0002] Alloy tape for cable shielding is a coating material wrapped around the outside of the cable core to prevent electromagnetic interference (EMI) and radio frequency interference (RFI) while providing physical protection and grounding functions.

[0003] The alloy tape for cable shielding is required to have excellent tensile strength, flexibility and corrosion resistance. It should be able to be unbroken during wrapping and flexible during laying. It should have a low corrosion rate when it is exposed to moisture during production, when the sheath is damaged during laying, or when the cable electroosmosis effect affects it, thereby protecting the cable core.

[0004] In the current technology development trend, aluminum alloy strips are gradually replacing copper alloy strips to reduce cable costs. However, compared with copper alloy strips, aluminum alloy strips are still insufficient in tensile strength, flexibility and corrosion resistance.

[0005] The current technology uses anodizing treatment to coat the surface of aluminum alloy strips, so that the aluminum alloy strips have corrosion resistance that is not inferior to that of high-quality copper alloy strips. However, the tensile strength and flexibility of aluminum alloy strips are still inferior to those of high-quality copper alloy strips. Therefore, how to simultaneously improve the strength and corrosion resistance of alloy strips for cable shielding has become one of the important research and development directions of aluminum alloy strips. Summary of the invention

[0006] In order to simultaneously improve the strength and corrosion resistance of an alloy strip for cable shielding, a rare earth high iron aluminum alloy strip is provided.

[0007] The above-mentioned first invention object of the present invention is achieved through the following technical solutions: A rare earth high iron aluminum alloy strip, comprising a strip body, wherein the strip body has the following components: Fe 4~6wt% Ce 1.1~1.3wt%; Y 0.7~0.9wt%; Mg 0.5~1wt%; Si 0.3~0.7wt%; Zr 0.1~0.3wt%; The rest is aluminum and unavoidable impurities; The surface of the strip body also includes a protective coating formed by first nitriding the surface of the strip body and then performing an anodic oxidation treatment.

[0008] By adopting the above technical solution, the aluminum matrix and high-content iron form a new strengthening framework, breaking through the Fe content limit of traditional aluminum alloys. The Fe-Al solid solution as a strength-enhancing phase forms a multi-scale strengthening network with the nano-scale Al-Fe-RE dispersed phase, achieving a synergistic improvement in matrix strength and ductility. On the other hand, the composite addition of cerium (1.2wt%) and yttrium (0.8wt%) produces a dual effect, reducing the grain boundary energy through surface activity, refining the grains to submicron level, preferentially forming Al3(RE,Fe) intermetallic compounds with Fe, inhibiting the excessive formation of brittle Al3Fe phase, and improving the alloy substructure stability to above 400℃; As a result, the mechanical properties of rare earth high iron aluminum alloy strips reach a better level in terms of flexibility, ductility and strength. In addition, Mg, Si, and Zr elements are added. Si reacts with rare earth to form RE-Si-Al composite phase with higher thermal stability. Zr-Fe coupling causes Zr atoms to be concentrated at the Al-Fe phase interface, thus improving the ability of the precipitate phase to resist coarsening. To reduce the adverse changes of the alloy metallographic phase caused by the temperature rise during the subsequent nitriding treatment of the rare earth high iron aluminum alloy strip, and to ensure that the mechanical properties of the rare earth high iron aluminum alloy strip are not attenuated when the nitriding treatment improves the corrosion resistance and wear resistance of the rare earth high iron aluminum alloy strip; Therefore, the rare earth high iron aluminum alloy strip of the present application has excellent mechanical properties and high corrosion resistance, and is well adapted to the cable core winding protection requirements.

[0009] Optionally: the nitriding treatment steps are as follows: After the strip body is subjected to surface pretreatment, it is subjected to plasma nitriding in an arc ion plating furnace to obtain a strip body after surface nitriding treatment.

[0010] Optional: The nitriding treatment process parameters are as follows: temperature is 400°C, nitriding atmosphere is 50sccm nitrogen, 250sccm argon, vacuum degree is 0.03mbar, initial substrate bias is -30V and then gradually adjusted to -180V, column arc current is set to 80A, and insulation treatment time is 8min.

[0011] By adopting the above-mentioned technical scheme, the surface of the strip body can be nitrided quickly and efficiently, reducing the influence of the temperature rise during the nitriding process on the alloy properties of the strip body, effectively forming a nitriding layer while ensuring the strength and toughness of the strip body, and improving the corrosion resistance and wear resistance of the surface of the rare earth high-iron aluminum alloy strip of this application.

[0012] Optionally: the strip surface pretreatment includes cleaning, drying, and spraying a pretreatment liquid, wherein the pretreatment liquid is a mixture of ethanol and dichloromethane.

[0013] By adopting the above technical scheme, ethanol can activate the free hydroxyl groups on the surface of the strip. The boiling point of dichloromethane is lower than that of ethanol, and it can evaporate before ethanol, replacing the atmosphere attached to the surface of the strip, thereby preventing the free hydroxyl groups on the surface of the strip from combining with oxygen in the air to be oxidized during activation, thereby ensuring that the free hydroxyl groups on the surface of the strip enter the nitriding treatment process in a highly active state, thereby making the nitriding more uniform and generating faster, and the corrosion resistance and wear resistance of the surface of the rare earth high-iron aluminum alloy strip of the present application are further improved.

[0014] Optional: The mass ratio of ethanol to dichloromethane in the spray pretreatment liquid is 10:(1.3~1.37).

[0015] By adopting the above technical solution, the amount of dichloromethane used is small and the pretreatment liquid has a good effect, thereby reducing the requirements for production environment conditions and waste gas treatment.

[0016] Optionally, the anodizing solution is a compound of sulfuric acid and citric acid.

[0017] By adopting the above technical solution, the passivation effect is good, the passivation film is more uniform and dense, and the corrosion resistance of the surface of the rare earth high iron aluminum alloy strip is good.

[0018] Optionally, the anodizing solution is a compound of sulfuric acid, citric acid and sodium citrate.

[0019] By adopting the above technical solution, the passivation effect is good, the passivation film is more uniform and dense, and the corrosion resistance of the surface of the rare earth high iron aluminum alloy strip is good.

[0020] Optionally: the thickness of the anodized layer in the protective coating is 0.35~0.38μm.

[0021] By adopting the above technical solution, the mechanical properties of the rare earth high iron aluminum alloy strip and the corrosion resistance of the strip surface are both excellent.

[0022] In summary, this application has at least the following beneficial effects: Compared with the prior art, the rare earth high iron aluminum alloy strip of the present application ensures good softness to meet the requirements of strip coating cable cores, while also having excellent mechanical properties and high corrosion resistance, and is well adapted to the requirements of cable core winding protection. DETAILED DESCRIPTION

[0023] Example 1 A rare earth high iron aluminum alloy strip comprises a strip body and a protective coating on the surface of the strip body.

[0024] The main components of the strip are: Fe 5.2wt%, Ce 1.22wt%, Y 0.86wt%, Mg 0.73wt%, Si 0.65wt%, Zr 0.22wt%, and the rest are aluminum and inevitable impurities.

[0025] The strip body is made of aluminum ingots and aluminum alloy ingots containing other elements as raw materials, and is obtained through smelting, alloying, casting, milling, rolling, and slitting. The thickness of the strip body is 0.15±0.02mm, and the width of the strip body is determined by the slitting size of the slitting step, which can be 1~20cm. Here, a strip body with a width of 8cm is taken as an example.

[0026] The protective coating is obtained by firstly subjecting the strip body to a nitriding treatment and then to an anodizing treatment.

[0027] The specific method of forming the protective coating is as follows: The surface of the strip body is cleaned, dried, and sprayed with a pretreatment liquid, the pretreatment liquid being a mixture of ethanol and dichloromethane in a mass ratio of 10:1.35, and the spraying amount of the pretreatment liquid is 8.4 g / m2; After the pretreatment liquid on the surface of the strip body evaporates, the strip body is sent to an arc plasma plating furnace for nitriding. The temperature in the furnace is 400°C, the vacuum degree in the furnace is 0.03 mbar, the nitriding atmosphere is 50 sccm nitrogen, 250 sccm argon, the initial bias voltage of the substrate is -30 V and then gradually adjusted to -180 V, the column arc current is set to 80 A, and the heat preservation treatment time is 8 min; After the treatment is completed, the strip body is allowed to cool naturally to obtain a strip body with nitrided surface; The strip body with nitrided surface is placed in an anodic treatment solution and powered on for anodizing treatment. The anodic treatment solution is a mixture of sulfuric acid, citric acid, sodium citrate, and water in a mass ratio of 10:3.4:1.5:90. The power-on current is 12A and the anodizing treatment time is 10 minutes. Thus, a protective coating film is formed on the surface of the strip body.

[0028] The thickness of the protective coating was tested to be 0.365±0.015μm.

[0029] Comparative Example 1 An aluminum alloy strip has no coating on its surface. The components of the aluminum alloy strip are 5.2wt% Fe, 1.22wt% Ce, 0.86wt% Y, 0.73wt% Mg, 0.65wt% Si, 0.22wt% Zr, and the rest are aluminum and inevitable impurities.

[0030] Aluminum alloy strips are made of aluminum ingots and aluminum alloy ingots containing other elements as raw materials, and are obtained through smelting, alloying, casting, milling, rolling, and slitting. The thickness of the strip body is 0.15±0.02mm, and the width of the strip body is determined by the slitting size of the slitting step, which can be 1~20cm. Here, a strip body with a width of 8cm is taken as an example.

[0031] Comparative Example 2 An aluminum alloy strip has no coating on its surface, and the components of the aluminum alloy strip are 0.1wt% Fe, 1.22wt% Ce, 0.86wt% Y, 0.73wt% Mg, 0.65wt% Si, 0.22wt% Zr, and the rest are aluminum and inevitable impurities.

[0032] Aluminum alloy strips are made of aluminum ingots and aluminum alloy ingots containing other elements as raw materials, and are obtained through smelting, alloying, casting, milling, rolling, and slitting. The thickness of the strip body is 0.15±0.02mm, and the width of the strip body is determined by the slitting size of the slitting step, which can be 1~20cm. Here, a strip body with a width of 8cm is taken as an example.

[0033] Comparative Example 3 An aluminum alloy strip comprises a strip body and a protective coating on the surface of the strip body.

[0034] The main components of the strip are Fe 0.1wt%, Ce 1.22wt%, Y 0.86wt%, Mg 0.73wt%, Si 0.65wt%, Zr 0.22wt%, and the rest are aluminum and inevitable impurities.

[0035] Aluminum alloy strips are made of aluminum ingots and aluminum alloy ingots containing other elements as raw materials, and are obtained through smelting, alloying, casting, milling, rolling, and slitting. The thickness of the strip body is 0.15±0.02mm, and the width of the strip body is determined by the slitting size of the slitting step, which can be 1~20cm. Here, a strip body with a width of 8cm is taken as an example.

[0036] The protective coating is obtained by anodizing the strip body.

[0037] The specific method of forming the protective coating is as follows: The surface of the strip body is cleaned and dried, and then immersed in an anodic treatment solution and powered on for anodizing treatment. The anodic treatment solution is a mixture of sulfuric acid, citric acid, sodium citrate, and water in a mass ratio of 10:3.4:1.5:90. The power-on current is 12A, and the anodizing treatment time is 10 minutes. Thus, a protective coating film is formed on the surface of the strip body.

[0038] The thickness of the protective coating was tested to be 0.365±0.015μm.

[0039] Comparative Example 4 An aluminum alloy strip comprises a strip body and a protective coating on the surface of the strip body.

[0040] The main components of the strip are Fe 5.2wt%, Ce 1.22wt%, Y 0.86wt%, Mg 0.73wt%, Si 0.65wt%, Zr 0.22wt%, and the rest are aluminum and inevitable impurities.

[0041] Aluminum alloy strips are made of aluminum ingots and aluminum alloy ingots containing other elements as raw materials, and are obtained through smelting, alloying, casting, milling, rolling, and slitting. The thickness of the strip body is 0.15±0.02mm, and the width of the strip body is determined by the slitting size of the slitting step, which can be 1~20cm. Here, a strip body with a width of 8cm is taken as an example.

[0042] The protective coating is obtained by anodizing the strip body.

[0043] The specific method of forming the protective coating is as follows: The surface of the strip body is cleaned and dried, and then immersed in an anodic treatment solution and powered on for anodizing treatment. The anodic treatment solution is a mixture of sulfuric acid, citric acid, sodium citrate, and water in a mass ratio of 10:3.4:1.5:90. The power-on current is 12A, and the anodizing treatment time is 10 minutes. Thus, a protective coating film is formed on the surface of the strip body.

[0044] The thickness of the protective coating was tested to be 0.365±0.015μm.

[0045] Comparative Example 5 An aluminum alloy strip, which differs from Example 1 in that the strip body has different composition. The strip body composition of Comparative Example 2 is 5.2wt% Fe, 0.73wt% Mg, 0.65wt% Si, 0.22wt% Zr, and the remainder is aluminum and unavoidable impurities.

[0046] Comparative Example 6 An aluminum alloy strip, which differs from Example 1 in that the strip body has different composition. The strip body composition of Comparative Example 3 is Fe 5.2wt%, Ce 1.22wt%, Y 0.86wt%, Mg 0.73wt%, Zr 0.22wt%, and the rest is aluminum and unavoidable impurities.

[0047] Comparative Example 7 An aluminum alloy strip, which differs from Example 1 in that the composition of the strip body is different. The strip body composition of Comparative Example 5 is Fe 5.2wt%, Ce 1.22wt%, Y 0.86wt%, Mg 0.73wt%, Si 0.65wt%, and the rest is aluminum and unavoidable impurities.

[0048] Comparative Example 8 An aluminum alloy strip, which differs from Example 1 in that the strip body has different composition. The strip body composition of Comparative Example 6 is Fe 5.2wt%, Ce 1.22wt%, Y 0.86wt%, Si 0.65wt%, Zr 0.22wt%, and the rest is aluminum and unavoidable impurities.

[0049] Example 2 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that the specific method for forming the protective coating is as follows: Clean and dry the surface of the strip body; The strip body to be treated is sent into an arc plasma plating furnace for nitriding. The temperature in the furnace is 400°C, the vacuum degree in the furnace is 0.03 mbar, the nitriding atmosphere is 50 sccm nitrogen, 250 sccm argon, the initial bias voltage of the substrate is -30V and then gradually adjusted to -180V, the column arc current is set to 80A, and the heat preservation treatment time is 8min; After the treatment is completed, the strip body is allowed to cool naturally to obtain a strip body with nitrided surface; The strip body with nitrided surface is placed in an anodic treatment solution and powered on for anodizing treatment. The anodic treatment solution is a mixture of sulfuric acid, citric acid, sodium citrate, and water in a mass ratio of 10:3.4:1.5:90. The power-on current is 12A and the anodizing treatment time is 10 minutes. Thus, a protective coating film is formed on the surface of the strip body.

[0050] The thickness of the protective coating was tested to be 0.365±0.015μm.

[0051] Example 3 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that in the specific method of forming the protective coating, the nitriding atmosphere in the arc plasma plating furnace is 30 sccm nitrogen and 270 sccm argon.

[0052] Example 4 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method of forming the protective coating, the nitriding atmosphere in the arc plasma plating furnace is 80 sccm nitrogen and 220 sccm argon.

[0053] Example 5 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that in the specific method for forming the protective coating, the insulation treatment time in the arc plasma plating furnace is 4 minutes.

[0054] Example 6 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that in the specific method for forming the protective coating, the insulation treatment time in the arc plasma plating furnace is 10 minutes.

[0055] Example 7 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the pretreatment liquid is a mixture of ethanol and dichloromethane in a mass ratio of 10:0.8.

[0056] Example 8 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the pretreatment liquid is a mixture of ethanol and dichloromethane in a mass ratio of 10:1.3.

[0057] Example 9 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the pretreatment liquid is a mixture of ethanol and dichloromethane in a mass ratio of 10:1.37.

[0058] Example 10 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the pretreatment liquid is a mixture of ethanol and dichloromethane in a mass ratio of 10:1.6.

[0059] Embodiment 11 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the anode treatment liquid is a mixture of sulfuric acid, citric acid and water in a mass ratio of 10:3.4:90.

[0060] Example 12 A rare earth high iron aluminum alloy strip, which differs from Example 1 in that in the specific method for forming the protective coating, the anode treatment liquid is a mixture of sulfuric acid and water in a mass ratio of 10:90.

[0061] Embodiment 13 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that the anodic treatment time in the specific formation method of the protective coating is 7 minutes, and the thickness of the protective coating is 0.10±0.02μm after inspection.

[0062] Embodiment 14 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that the anodic treatment time in the specific formation method of the protective coating is 18 minutes, and the thickness of the protective coating is 0.20±0.02μm after inspection.

[0063] Embodiment 15 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that the strip body components are Fe 4wt%, Ce 1.1wt%, Y 0.7wt%, Mg 0.5wt%, Si 0.3wt%, Zr 0.1wt%, and the rest are aluminum and unavoidable impurities.

[0064] Example 16 A rare earth high iron aluminum alloy strip, which is different from Example 1 in that the strip body components are Fe 6wt%, Ce 1.3wt%, Y 0.9wt%, Mg 1wt%, Si 0.7wt%, Zr 0.3wt%, and the rest are aluminum and unavoidable impurities; The aluminum alloy strips obtained in Examples 1 to 16 and Comparative Examples 1 to 8 were tested.

[0065] Tensile strength: Tested according to GB / T 228.1-2021 Tensile test of metallic materials Part 1: Room temperature test method.

[0066] Vickers hardness: Tested in accordance with GB / T 4340.1-2024 Metallic materials Vickers hardness test Part 1: Test method.

[0067] Corrosion resistance: The test is carried out according to "GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test". The test conditions are set to 8wt NaCl solution, pH 7.0, ambient temperature 35°C, test time 108h, and the test results are expressed as corrosion rate.

[0068] The test results are shown in Table 1 below.

[0069] Table 1. Test results of Examples 1 to 16 and Comparative Examples 1 to 8

[0070] Combined with the above table, the aluminum alloy strips of Comparative Example 1 and Comparative Example 2 are not treated to add protective coating. The Fe content in the aluminum alloy strip of Comparative Example 1 is significantly higher than that of Comparative Example 2. In the test results, the tensile strength of the aluminum alloy strip of Comparative Example 1 is improved compared with that of Comparative Example 2, but at the same time, the hardness of Comparative Example 1 is also improved compared with that of Comparative Example 1, and the corrosion rate of Comparative Example 1 is significantly increased compared with that of Comparative Example 2. Therefore, it can be seen that the increase of Fe content in the existing conventional aluminum alloy strip without protective coating will increase the strength of the strip, but will significantly weaken the flexibility and corrosion resistance of the strip, which is unfavorable in the field of cable core wrapping materials.

[0071] By comparing Comparative Example 2 and Comparative Example 3, it can be seen that Comparative Example 3 was anodized on the basis of Comparative Example 2, and the strength and hardness of the two are similar, while the corrosion resistance of Comparative Example 3 is significantly improved compared with that of Comparative Example 2, which is consistent with the effect of anodizing treatment on the corrosion resistance of strip in the field.

[0072] By comparing Comparative Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 was anodized on the basis of Comparative Example 1, and the strength and hardness of the two are similar, but the corrosion resistance of Comparative Example 4 is lower than that of Comparative Example 1. The applicant analyzed the anodic protective film obtained by anodizing treatment and found that more Fe hydroxide and oxide hydrate complexes were mixed into the anodic protective film of Comparative Example 4, resulting in a decrease in the corrosion resistance of the anodic protective film of Comparative Example 4. Therefore, for aluminum alloy strips, excessively high Fe content has an adverse effect on the anti-corrosion effect brought by the anodizing treatment of the strip.

[0073] Combining Example 1 and Comparative Examples 1 to 4, it can be seen that the tensile strength of the aluminum alloy strip of Example 1 of the present application is better than that of Comparative Examples 1 to 4. At the same time, the hardness of Example 1 is similar to that of Comparative Examples 1 and Comparative Example 4 with high Fe content in Comparative Examples 1 to 4, and the corrosion rate of Example 1 is significantly lower than that of Comparative Examples 1 to 4. Therefore, the rare earth high-iron aluminum alloy strip of Example 1 in the present application, compared with the prior art, ensures good softness to meet the requirements of strip coating cable cores, and also has excellent mechanical properties and high corrosion resistance, and is well adapted to the cable core winding protection requirements.

[0074] Combined with Example 1 and Comparative Examples 5 to 8, Example 1 and Comparative Examples 5 to 8 are all aluminum alloy strips with high Fe content.

[0075] In Example 1 of the present application, in addition to a high content of Fe, Ce, Y, Mg, Si, and Zr are added to the strip material, and the strip material is first subjected to nitriding treatment and then anodized; In Comparative Example 5, in addition to a high content of Fe, Mg, Si, and Zr are added to the strip, and the strip is first nitrided and then anodized; In Comparative Example 6, in addition to a high content of Fe, Ce, Y, Mg, and Zr are added to the strip, and the strip is first nitrided and then anodized; In Comparative Example 7, in addition to a high content of Fe, Ce, Y, Mg, and Si are added to the strip, and the strip is first nitrided and then anodized; In Comparative Example 7, in addition to a high content of Fe, Ce, Y, Si and Zr are added to the strip, and the strip is first nitrided and then anodized.

[0076] In the test results, the tensile strength of Example 1 is significantly greater than that of Comparative Example 5, the hardness of Example 1 is not higher than that of Comparative Example 5, and the corrosion rate of Example 1 is significantly lower than that of Comparative Example 5; The tensile strength of Example 1 is significantly greater than that of Comparative Example 6, the hardness of Example 1 is not higher than that of Comparative Example 6, and the corrosion rate of Example 1 is lower than that of Comparative Example 6; The tensile strength of Example 1 is significantly greater than that of Comparative Example 7, the hardness of Example 1 is not higher than that of Comparative Example 7, and the corrosion rate of Example 1 is lower than that of Comparative Example 7; The tensile strength of Example 1 is significantly greater than that of Comparative Example 7, the hardness of Example 1 is not higher than that of Comparative Example 7, and the corrosion rate of Example 1 is lower than that of Comparative Example 7.

[0077] It can be seen that, compared with the prior art, Example 1 of the present application can achieve good softness that meets the requirements of the tape-coated cable core, and at the same time also has excellent mechanical properties and high corrosion resistance. The reason is the synergistic effect of the following points: 1. With high Fe content and the addition of rare earth elements, the aluminum matrix and high-content iron form a new reinforcement framework, breaking through the Fe content limitation of traditional aluminum alloys. The Fe-Al solid solution as a strength-enhancing phase forms a multi-scale reinforcement network with the nanoscale Al-Fe-RE dispersed phase, achieving a synergistic improvement in matrix strength and ductility.

[0078] 2. The surface of the strip is first nitrided and then anodic protected. The surface nitriding treatment changes the Fe alloy phase on the surface of the strip, enhances the corrosion resistance of the strip and eliminates the adverse effects of high Fe content on the corrosion resistance and anodic oxidation of the strip.

[0079] 3. Rare earth elements selected Ce and Y compound and added Mg, Si, and Zr. The composite addition of cerium (1.2wt%) and yttrium (0.8wt%) produces a dual effect. It reduces the grain boundary energy through surface activity, refines the grains to submicron level, preferentially forms Al3(RE,Fe) intermetallic compounds with Fe, inhibits the excessive generation of brittle Al3Fe phase, and improves the alloy substructure stability to above 400℃; Si reacts with rare earth to form RE-Si-Al composite phase with higher thermal stability, Zr-Fe coupling makes Zr atoms segregate at the Al-Fe phase interface, improves the ability of precipitated phase to resist coarsening, Mg coordinates to improve the phase solubility between the components, and optimizes the metallographic distribution, thereby reducing the adverse changes of the alloy metallographic phase caused by temperature rise during nitriding treatment, and ensuring that the mechanical properties of rare earth high iron aluminum alloy strip are not attenuated when the corrosion resistance and wear resistance of rare earth high iron aluminum alloy strip are improved during nitriding treatment; Only when the three are combined and coordinated with each other can the performance of the aluminum alloy strip of the present application be achieved. The three are indispensable. For example, comparative examples 6 to 8 lack the addition of Si, Zr, and Mg, respectively, resulting in a decrease in tensile strength after nitriding treatment compared with embodiment 1, and an increase in hardness, which is not conducive to the winding and coating requirements of cable zinc.

[0080] Combining Example 1 with Example 2 and Examples 7 to 10, it can be seen that the hardness of Example 1 and Examples 8 to 10 is lower than that of Example 2, and the corrosion rate of Example 1 and Examples 7 to 10 is lower than that of Example 2; therefore, the pretreatment liquid compounded with ethanol and dichloromethane used in the present application can activate the free hydroxyl groups on the surface of the strip and reduce the oxidation of the strip, making the nitriding more uniform and generating faster, and the corrosion resistance and wear resistance of the surface of the rare earth high iron aluminum alloy strip of the present application are further improved.

[0081] In addition, the corrosion rates of Example 1, Example 8, Example 9, and Example 10 are lower than that of Example 7. When the mass ratio of ethanol to dichloromethane in the pretreatment liquid is 10: (1.3-1.37), the effect is better, and the amount of dichloromethane used is small, which reduces the production environment conditions and waste gas treatment requirements.

[0082] By comparing Example 1 with Examples 3 to 6, it can be seen that the tensile strength of Example 1 is greater than that of Examples 3 to 4, and the corrosion rate of Example 1 is lower than that of Examples 3 to 4; the tensile strengths of Example 1 and Example 5 are similar, and the corrosion rate of Example 1 is lower than that of Example 5; the corrosion rates of Example 1 and Example 6 are similar, and the tensile strength of Example 6 is lower than that of Example 1; therefore, the nitriding treatment parameters in this application are controlled as follows: the temperature is 400°C, the nitriding atmosphere is 50sccm nitrogen, 250sccm argon, the vacuum degree is 0.03mbar, the initial bias voltage of the substrate is -30V and then gradually adjusted to -180V, the column arc current is set to 80A, and the insulation treatment time is 8min, and the obtained aluminum alloy strip has better comprehensive performance.

[0083] Combining Example 1 and Examples 11-12, it can be seen that the corrosion rate of Example 1 is lower than that of Example 11, and the corrosion rate of Example 11 is lower than that of Example 12. Therefore, the treatment effect is better when the anodizing liquid in the present application is a compound of sulfuric acid, citric acid, and sodium citrate or is sulfuric acid or citric acid.

[0084] Combining Example 1 and Examples 13-14, it can be seen that the three can obtain protective coatings of different thicknesses by adjusting the anodizing treatment time. The corrosion rates of Example 1 and Example 14 are lower than that of Example 13. Therefore, in the present application, the protective coating obtained by first nitriding treatment and then anodizing treatment has a thickness of 0.35-0.38 μm, which has good protection performance, and low production time cost and energy consumption cost.

[0085] In addition, the present application has other better solutions for the research process of adjusting the alloy composition of the strip body, such as Examples 15~16. The tensile properties, hardness, and corrosion resistance of Examples 15~16 are similar to those of Example 1, and their comprehensive performance has significant improvement over the prior art. The improvement effect of the present application can be achieved by controlling the composition of the strip body in the following range: Fe 4~6wt%, Ce 1.1~1.3wt%, Y 0.7~0.9wt%, Mg 0.5~1wt%, Si 0.3~0.7wt%, Zr 0.1~0.3wt%, and the rest are aluminum and unavoidable impurities.

[0086] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A rare earth high iron aluminum alloy strip, characterized in that: It includes a strip body, and the strip body has the following components: Fe 4~6wt% Ce 1.1~1.3wt%; Y 0.7~0.9wt%; Mg 0.5~1wt%; Si 0.3~0.7wt%; Zr 0.1~0.3wt%; The rest is aluminum and unavoidable impurities; The surface of the strip body also includes a protective coating formed by first nitriding the surface of the strip body and then performing an anodic oxidation treatment.

2. The rare earth high iron aluminum alloy strip according to claim 1, characterized in that: The nitriding treatment steps are as follows: After the strip body is subjected to surface pretreatment, it is subjected to plasma nitriding in an arc ion plating furnace to obtain a strip body after surface nitriding treatment.

3. The rare earth high iron aluminum alloy strip according to claim 1, characterized in that: The nitriding process parameters are as follows: temperature is 400°C, nitriding atmosphere is 50sccm nitrogen, 250sccm argon, vacuum is 0.03mbar, substrate initial bias is -30V and then gradually adjusted to -180V, column arc current is set to 80A, and insulation treatment time is 8min.

4. The rare earth high iron aluminum alloy strip according to claim 2, characterized in that: The strip surface pretreatment includes cleaning, drying, and spraying a pretreatment liquid. The pretreatment liquid is a mixed liquid of ethanol and dichloromethane.

5. The rare earth high iron aluminum alloy strip according to claim 4, characterized in that: The mass ratio of ethanol to dichloromethane in the spray pretreatment liquid is 10:(1.3-1.37).

6. The rare earth high iron aluminum alloy strip according to claim 4, characterized in that: The anodizing solution is prepared by mixing sulfuric acid and citric acid.

7. The rare earth high iron aluminum alloy strip according to claim 4, characterized in that: The anodizing liquid is prepared by mixing sulfuric acid, citric acid and sodium citrate.

8. The rare earth high iron aluminum alloy strip according to claim 1, characterized in that: The thickness of the anodized layer in the protective coating is 0.35-0.38 μm.

Citation Information

Patent Citations

  • Rare earth high-speed rail aluminum alloy conductor materials

    CN102262913A

  • Rear earth aluminum alloy material

    CN102347092A

  • High-magnetic energy product high-speed brushless motor electric core material and preparation method thereof

    CN109576557A

  • High-strength aluminum alloy profile for brake chamber and processing technology of high-strength aluminum alloy profile

    CN114672684A

  • Enhanced 606X series aluminum alloy and preparation and profile processing method thereof

    CN115572870A